Pre- and intraoperative diagnostic requirements, benefits and risks of minimally invasive and robotic surgery for neuroendocrine tumors of the pancreas. Issue 5 (October 2019) - Gharios, Joseph; Hain, Elisabeth; Dohan, Anthony; Prat, Fréderic; Terris, Benoit; Bertherat, Jérôme; Coriat, Romain; Dousset, Bertrand; Gaujoux, Sébastien
Abstract : Pancreatic neuroendocrine tumours (PanNET) are rare tumours, accounting for 1%–2% of all pancreatic neoplasms. These tumors are classified as functioning neuroendocrine tumours (F-PanNETs) or non-functioning (NF-PanNETs) depends on whether the tumour is associated with clinical hormonal hypersecretion syndrome or not. In the last decades, diagnosis of PanNETs has increased significantly due to the widespread of cross-sectional imaging. Whenever possible, surgery is the cornerstone of PanNETs management and the only curative option for these patients. Indeed, after R0 resection, the 5-year overall survival rate is around 90–100% for low grade lesions but significantly drops after incomplete resections. Compared to standard resections, pancreatic sparing surgery, i.e. enucleation and central pancreatectomy, significantly decreased the risk of pancreatic insufficiency. It should be performed in patients with good general condition and normal pancreatic function to limit the operative risk and enhance the benefit of surgery. Nowadays, due to many known advantages of minimally invasive surgery, there is an ongoing trend towards laparoscopic and robotic pancreatic surgery. The aim of this study is to describe the pre- and intraoperative diagnostic requirements for the management of PanNETs and the benefits and risks of minimally invasive surgery including laparoscopic and robotic approach in view of the recent literature.